2011
DOI: 10.1371/journal.pone.0024447
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Sialomucin and Sulfomucin Expression and Hydrogenotrophic Microbes in the Human Colonic Mucosa

Abstract: The colonic mucus layer is comprised primarily of acidomucins, which provide viscous properties and can be broadly classified into sialomucins or sulfomucins based on the presence of terminating sialic acid or sulfate groups. Differences in acidomucin chemotypes have been observed in diseases such as colorectal cancer and inflammatory bowel disease, and variation in sialo- and sulfomucin content may influence microbial colonization. For example, sulfate derived from sulfomucin degradation may promote the colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 31 publications
3
65
1
Order By: Relevance
“…In order to achieve this, 25 colonic tissues consisting of 3 normal and 22 different graded colonic cancers, were histocemically stained to assess the types of mucins. Following histochemical staining (diastase-AB/PAS), it was observed that the normal colonic tissue demonstrated predominance of acidic mucin (80%) and scanty neutral mucin (20%), confirming what have been made already [15,20] that acidic mucin is copiously present in the colon for the primary role of viscosity. A striking pattern, contrary to the amount of mucins in normal colon, was observed in low graded well-differentiated adenocarcinomas of the colon-a decrease in acid mucin (73.7%) and an increase in the neutral mucin expression (26.3%) as compared to the normal colon mucin variant expression (Table 2).…”
Section: Discussionsupporting
confidence: 74%
“…In order to achieve this, 25 colonic tissues consisting of 3 normal and 22 different graded colonic cancers, were histocemically stained to assess the types of mucins. Following histochemical staining (diastase-AB/PAS), it was observed that the normal colonic tissue demonstrated predominance of acidic mucin (80%) and scanty neutral mucin (20%), confirming what have been made already [15,20] that acidic mucin is copiously present in the colon for the primary role of viscosity. A striking pattern, contrary to the amount of mucins in normal colon, was observed in low graded well-differentiated adenocarcinomas of the colon-a decrease in acid mucin (73.7%) and an increase in the neutral mucin expression (26.3%) as compared to the normal colon mucin variant expression (Table 2).…”
Section: Discussionsupporting
confidence: 74%
“…Sulfomucins are a crucial source of sulfate for sulfate-reducing bacteria and play a prominent protective role by increasing mucus viscosity (Croix et al, 2011). It is suggested that sulfomucins are able to reduce the rate at which microflora degrade mucins (Robertson and Wright, 1997) as the high sulfate content of sulfomucins decrease its susceptibility to bacterial glycosidases, limiting the rate and extent of mucin degradation (Hino et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…24) The mucosal surfaces of the human intestine contain negatively charged molecules, including sialic acid and sulfate groups. 25,26) Hence, it was suggested that extracellular histones released from the cells by apoptosis bind to the negatively charged surfaces of adjacent viable cells. 27) We detected histone H3 in human colonic mucus, indicating highly basic histones other than histone H1 would also be released into the lumen from intestinal epithelial cells and localized on the mucosal surfaces by electrostatic interaction.…”
Section: Discussionmentioning
confidence: 99%